Dwi Fungsi ABRI : Melacak Sejarah Keterlibatan ABRI dalam Kehidupan Sosial Politik dan Perekonomian Indonesia - Anwar Anwar (Jurnal Adabiya, 2018)
This paper examines the historical roots of the emergence of the involvement of the Armed Forces of the Republic of Indonesia (ABRI) in the socio-political field, especially several reasons that form the basis of government policy to involve ABRI in the socio-political and economic fields, as well as ABRI’s own efforts to play a role in these fields. This historical approach research concluded that ABRI’s involvement in the socio-political field in Indonesia had begun since the government of Guided Democracy under President Soekarno. Politically, the reason for Soekarno’s inclusion of the military in his government structure was due to the failure of civilian politicians in formulating state ideology with no agreement between parties in the constituent assembly. This failure is considered to endanger national political stability and threaten the integrity of the country. For this reason, President Soekarno recruited the military to balance civilian politicians in his government. Along with its involvement in the socio-political field, ABRI also plays a role in socio-economics. Although at first, this role was limited to securing national private companies which were legacies of foreign companies, but during the New Order government, the dual function of ABRI was confirmed and its role was wider. Almost all strategic economic sectors are controlled by ABRI.